Late-Pleistocene and Holocene palynology in southeastern Québec - Mott, R. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Several relative and absolute pollen profiles from the Appalachian Region outline the vegetational history of the region. The earliest reliable date of 11,200 radiocarbon years BP, from the watershed area of the Mégantic Hills on the Québec-Maine border, dates the spruce pollen maximum, indicative of spruce woodland conditions. A second site in the same area shows tundra conditions existed prior to this time, but no radiocarbon dates are available to indicate the length of time these conditions persisted. About 10,000 radiocarbon years BP or less, the character of the vegetation changed and closed forest conditions prevailed. Spruce was still present, but balsam fir and birch increased and other deciduous species appeared. The continued increase in thermophilous deciduous species and hemlock and white pine during early- and mid-Holocene resulted in forests in which these taxa were more prominent than at present. An increase in spruce and decline in thermophilous taxa in the last few millenia produced the extant forests types.